2015
DOI: 10.1186/s13099-015-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Non-Typhoidal Salmonella in poultry meat and diarrhoeic patients: prevalence, antibiogram, virulotyping, molecular detection and sequencing of class I integrons in multidrug resistant strains

Abstract: BackgroundThe worldwide increase of food-borne infections with antibiotic resistant pathogens constitutes a major public health problem. Therefore, this study aimed to determine the prevalence, antibiogram, virulence genes profiles and integron characteristics of non-typhoidal Salmonella spp. isolated from poultry meat and diarrhoeic patients in Egypt.MethodsA total of 150 samples comprising (100 poultry meat and 50 diarrhoeic patients’ stool) were examined for the presence of Salmonella spp. using culture met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
41
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 33 publications
13
41
6
1
Order By: Relevance
“…They were much higher than that previously reported by Gharieb et al (2015) in Egypt, who detected Salmonella spp. with a prevalence of 14% in chicken meat.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…They were much higher than that previously reported by Gharieb et al (2015) in Egypt, who detected Salmonella spp. with a prevalence of 14% in chicken meat.…”
Section: Resultscontrasting
confidence: 70%
“…with a percentage of 4%. In this regard, Gharieb et al (2015) reported a similar prevalence (4%) of Salmonella in human stools in Egypt. Moreover, Murugkar et al (2005) reported nearly similar prevalence in India.…”
Section: Resultsmentioning
confidence: 64%
“…The detection of these genes by PCR has been widely used as a predictive measure for Salmonella virulence (32,33). sptP was not amplified among S. Mbandaka and Worthington isolates.…”
Section: Discussionmentioning
confidence: 99%
“…NTS cause a gastrointestinal infection which presents as inflammation manifested with diarrhea, nausea, vomiting, and headache [13]. The severity of infection varies depending on two factors; the serotype implicated and the health of the patient [14].…”
Section: Pathogenesismentioning
confidence: 99%
“…An Egyptian study conducted on Salmonella isolates from human and animals showed an increasing rate of antimicrobial resistance among NTS isolates between 2014 and 2015, in particular to erythromycin and tetracycline, and amoxicillin-clavulanic acid. This resistance was linked to over-use of antimicrobials in livestock [13]. In Kenya, among 342 NTS isolates, the prevalence of MDR strains reached 42% during 2003 [47].…”
Section: Antimicrobial Resistant Salmonella Across Africamentioning
confidence: 99%